The Hellenic Longitudinal Investigation of Aging and Diet (HELIAD): Rationale, Study Design, and Cohort Description. - Dardiotis, Efthimios; Kosmidis, Mary H; Yannakoulia, Mary; Hadjigeorgiou, Georgios M; Scarmeas, Nikolaos (Neuroepidemiology, 2014)
Background: Accumulating epidemiological evidence from several populations supports the important role of the Mediterranean-type diet (MeDi) in reducing the risk for age-related diseases such as Alzheimer's disease (AD). However, the relevant literature is clearly deficient for most Mediterranean countries that more closely adhere to the originally described MeDi. Greece resides in the Mediterranean basin, and older generations traditionally adhere to a MeDi. Methods: We here present the design and the preliminary baseline characteristics of the Hellenic Longitudinal Investigation of Aging and Diet (HELIAD). The HELIAD is a population-based, multidisciplinary, collaborative study designed to estimate the prevalence and incidence of AD, other dementias, mild cognitive impairment, and other neuropsychiatric conditions of aging in the Greek population and to investigate associations between nutrition and cognitive dysfunction/age-related neuropsychiatric diseases in this Mediterranean population. The study also ascertains several demographic, medical, social, environmental, clinical, nutritional, and neuropsychological determinants and lifestyle activities. Results: In total, 1,050 participants of a random sample have already completed the initial evaluation. The subjects were, on average, 73.4 (SD = 6.0) years old, 60% of the sample were female, and most of the participants were poorly educated with an average of 5.41 (SD = 3.5) years of education. The performance on the neuropsychological tests was equivalent to the average scores of previous normative Greek samples. More than one third of the population under investigation was considered to be at high risk for malnutrition. Conclusions: The HELIAD may provide important data for expanding our knowledge regarding the prevalence, incidence, and risk factors of AD and several other neuropsychiatric diseases in the Mediterranean region. © 2014 S. Karger AG, Basel.